13-2x-5x+9=

Simple and best practice solution for 13-2x-5x+9= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13-2x-5x+9= equation:


Simplifying
13 + -2x + -5x + 9 = 0

Reorder the terms:
13 + 9 + -2x + -5x = 0

Combine like terms: 13 + 9 = 22
22 + -2x + -5x = 0

Combine like terms: -2x + -5x = -7x
22 + -7x = 0

Solving
22 + -7x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-22' to each side of the equation.
22 + -22 + -7x = 0 + -22

Combine like terms: 22 + -22 = 0
0 + -7x = 0 + -22
-7x = 0 + -22

Combine like terms: 0 + -22 = -22
-7x = -22

Divide each side by '-7'.
x = 3.142857143

Simplifying
x = 3.142857143

See similar equations:

| 2.5x-(40+1.75x)=550 | | 0.7=0.4+x-0.35 | | 20x+12=0 | | 16+2(x+4)(x-4)-x=-x+16 | | 6(y-1)-2y=2(2y-3) | | 0.7=0.4+P(B)-0.35 | | .25x-.75y=-1 | | 7.4x-4-5.2x=2.6 | | 4(5x+4)=3x+36+7x | | x^2+3y=-1 | | 8(m+6)+4=36+5m | | -3.6x+1.3=-16.7 | | 21x+6=23x-2 | | G(x)=x^2-x-5 | | -2.1-1.5=x+1.3 | | 3=t+5-3t | | 4x-5=6x+3 | | 2(x+5)=2x-5 | | 6=v+0.84 | | -50-0.25=-75 | | 110x=90(2-x) | | 1.29+3.9-9.99+6.1= | | X-3(x-5)=2x-11 | | 5y-x=-1 | | W^3+w^2-2w=8 | | 6a-3ab-4ak+2bk= | | 3x+17=4x+6 | | W^3+w^2-2w-8=0 | | -1.8+n=2.6-3.9 | | 3+35x=21x+11 | | 1x-10=4x-25 | | 36x^3-21x^2-30=0 |

Equations solver categories